Peran dan Kontribusi Curahan Waktu Kerja Wanita Pada Usahatani Karet (Hevea brasiliensis) di Desa Pondok Meja Kecamatan Mestong Kabupaten Muaro Jambi - Asmaida, Asmaida; Hardita, Risma (Universitas Batangahari Jambi, 2024)
The peasant woman in Pondok Meja Village works in the rubber plantation to help her husband to manage the rubber farming business and save for their family. Women have an important role in farming activities so they have to divide their time at work and take care of the household so that research needs to be done first. This research was conducted because they wanted to see how and what types of activities are carried out by peasant women in rubber farming, how much contribution the outpouring of work time of peasant women in rubber farming in Pondok Meja Village, Mestong District, Muaro Jambi Regency. A total of 30 farmer households (RTP) were sampled using the simple random sampling method. The conclusion of this result showsÂ that the pattern of the labor division between men (husbands) and peasant women (wives) has become a practiced habit until now. The types of activities carried out by peasant women in rubber farming are weeding, rubber tapping, sap collection, to sap sales. The contribution of the outpouring of working time of peasant women in rubber farming is 46.32%, so it is assumed that the contribution of the outpouring of working time of peasant women (wives) in rubber farming has a very high contribution.Â